Philosophical connotations of the leadership phenomenon - S. M. Heiko; O. D. Lauta (Ukrainian Cultural Studies, 2020)
The article focuses on the phenomenon of leadership in philosophical discourse. Philosophical retrospection of the concept of "leadership" as a philosophical phenomenon and its systematic analysis is carried out. Philosophical connotations of the phenomenon of leadership in the dynamics of social and political processes of modern times are being defined. In modern society, the well-formed image of leaders of organizations, movements and etcetera an important role. Leadership is a universal phenomenon of social life. It is present in any sphere of human activity that requires stratification: the separation of leaders and subordinates, leaders and followers. In modern science, where there is a commonality of initial positions, leadership is characterized by ambiguity: as a social relationship of domination and subordination in a group or organization (sociology); as a characteristic of the figure of a leader and its impact on others (psychology); as effective and successful innovations in business, dominance in enterprise performance (economy); as developing vision, decision-making, empowerment and direction of people towards specific goals (management); as a process of human interaction in which authoritative people wield real power, exerting legitimate influence on a society that voluntarily gives them part of its political power and rights (political science). The essence of leadership reveals its numerous concepts and theories that have evolved in the history of philosophy and social philosophy. Classical theorists tried to understand and develop the ideal concepts of leadership. Modern researchers are not analyzing the ideal of leadership, but what it is. The philosophical understanding of leadership can be seen, first, as a form of power held by one individual or group of individuals; secondly, as a social position of decision-making; thirdly, as an influence on others.